The Low Countries History Yearbook 1982 - Belder, J. De. author. aut Link
VII, 205 p.
Keywords: The present volume, number 15 of the Acta Historiae Neerlandicae - which have been appearing since 1978 under the title The Low Countries History Yearbook - is the last of the series. Economic reasons force the publishers to discontinue it. This is a matter for regret. Both the editors of the Yearbook and the board of the Nederlands Historisch Genootschap, under the auspices of which it has been published, are con vinced that the books serve a useful purpose. We hope that in the future more favour able circumstances will enable Dutch and Flemish historians to start a second series. We feel, however, that the Yearbook should not be allowed to disappear com pletely. In our opinion, one of its most attractive features has been the 'Survey of recent historical works on Belgium and the Netherlands published in Dutch.' It is the intention of the Nederlands Historisch Genootschal'. to seek means to continue this in another form, probably in that of pamphlets appearing every two years and written by the same, or a similar, group of experts. In that way we may be able to provide a useful service to our colleagues abroad.